Manfaat Prebiotik Tepung Pisang Kepok (Musa paradisiaca formatypica) terhadap Pertumbuhan Probiotik Lactobacillus casei secara In Vitro - Hardisari, Ratih; Amaliawati, Nur (POLTEKKES KEMENKES YOGYAKARTA, 2016)
This background reviewed cases of diarrhea, one of health problems related to the digestive tract and caused by an imbalance in intestinal microflora. Probiotics are microorganisms that can be used to balance the intestinal microflora’s population. Prebiotics are nutrients required for the growth of good bacteria in human’s intestine. Kepok banana (Musa paradisiaca formatypica) that contains inulin and FOS is a natural source of prebiotics. The purpose of this study is to observe the effect of various concentrations of kepok banana flour (Musa paradisiaca formatypica) on the growth of probiotic bacterium Lactobacillus casei. In order to observe the prebiotic activity of Lactobacillus casei, post-test with control group design method is used toward the kepok banana flour. The amounts of kepok banana flour concentration used are varied, which are 2%, 4%, 6%, 8 %, and 10%. As much as 30 data was resulted from this research that was, later, descriptively analyzed with One-Way ANOVA test using SPSS 16.0 for Windows. The research’s finding shows the average numbers of bacterium Lactobacillus casei (the number of bacteria x 107CFU/ml) produced in the media with the addition of MPF’s concentrations of 2%, 4%, 6%, 8%, and 10% are, respectively, 29187,5 ; 42491,67 ; 52225 ; 89879,17 and 155108,33. This research also obtained a significance value of 0.000 of the One-way Anova test. The conclusion of this study is that there is an in vitro effect of adding various concentrations of kepok banana flour on the growth of probiotic bacterium Lactobacillus casei.